DRYING KINETICS OF HOT-AIR DRIED BEEF MEAT: APPLICATION OF MATHEMATICAL MODELS, ENERGY CONSUMPTION, AND COLOR CHARACTERISTICS - Ismail, O.; Kocabay, O. G. (BEGELL HOUSE INC, 2018)
In this study, the effect of different drying conditions on the thermal and physical properties of beef meat samples was studied. The drying experiments were carried out at three different temperatures (40, 50, and 60 degrees C) with a constant air flow rate of 1 m/s. Moisture transfer from beef meat samples was described by applying Fick's diffusion model. Effective moisture diffusivity of beef meat samples during experiments was achieved to be (4.56-11.98) x 10(-10)m(2)/s. The activation energy of the samples was found as 42.93 kJ/mol. The results showed that the Alibas model had the best performance in predicting the moisture ratio. The highest and lowest values of energy consumption were calculated to be equal to 10.83 and 5.32 kWh, respectively. After drying, the total color difference increased. The changes in the sample surface color after drying were also measured, and the total color change Delta E of the samples at all temperatures and after each drying process was greater than 11.
Keywords: beef meat; moisture diffusivity; activation energy; energy consumption; color; QUALITY; TECHNOLOGIES; SLICES; Thermodynamics